Jurisdictional Enforcement Of Cyber Crime Against Lottery Scam - Jesslyn Elisandra Harefa; Rahmayanti Rahmayanti; Eri Siswanto; Faruq Rozy; Ireny Natalia Putri Sihite (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Cyber crime is increasingly prevalent with various modes, one of which is fraud under the guise of lottery prizes. This crime not only causes financial losses but also complicates law enforcement officials in terms of jurisdiction, especially if the perpetrators and victims are located in different regions, even across countries. This research aims to analyze how jurisdiction is enforced in dealing with cyber-based fraud crimes and examine the effectiveness of national legal instruments against the digital fraud mode. The research method used is a normative juridical approach with secondary data analyzed descriptively-analytically. The results show that jurisdictional enforcement in this case still faces technical and legal challenges, especially in the aspect of inter-state coordination and the limitations of domestic legal instruments in reaching cross-border perpetrators. Strengthening international cooperation and updating national regulations are needed to anticipate the dynamics of cybercrime.